2019
DOI: 10.1108/ijmhsc-09-2018-0064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and experiences of food insecurity among immigrant women connected to perinatal programs at a community-based organization in Edmonton, Canada

Abstract: PurposeThe purpose of this paper is to investigate the prevalence of household food insecurity among immigrant women connected to perinatal programs offered through a community-based organization in Edmonton, and to explore their experiences in coping with food insecurity.Design/methodology/approachThis study utilized a mixed methods research design. A community-based participatory research approach was used to engage health workers who were connected to immigrant women and families through the Multicultural H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Food-related strategies included rationing meals and relying on nutritionally poor, yet affordable and satiating foods. This finding is consistent with another study that explored the strategies of food-insecure perinatal women (Quintanilha et al, 2019 ). Although several other studies have demonstrated that strategies such as these are employed by food-insecure mothers when not pregnant (Gross et al, 2019 ; McKenzie & McKay, 2017 ; Weinstein et al, 2019 ), the present study is the first in Australia to highlight that these methods are applied in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Food-related strategies included rationing meals and relying on nutritionally poor, yet affordable and satiating foods. This finding is consistent with another study that explored the strategies of food-insecure perinatal women (Quintanilha et al, 2019 ). Although several other studies have demonstrated that strategies such as these are employed by food-insecure mothers when not pregnant (Gross et al, 2019 ; McKenzie & McKay, 2017 ; Weinstein et al, 2019 ), the present study is the first in Australia to highlight that these methods are applied in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…A second key finding was that food-insecure pregnant women were constantly aware of their struggles, always mindful of the threat of deprivation, a finding also evident in research by Quintanilha et al ( 2019 ). The omnipresent exhaustion that can attend the FI experience is heightened during pregnancy, when the importance of healthy eating is pitted against the practicality of affording it.…”
Section: Discussionmentioning
confidence: 62%
“…21 Findings from this review briefly describe how food access and food availability are implicated in the acceleration of dietary acculturation. 34,[36][37][38] Additionally, existing research has demonstrated how age, socioeconomic status, and the amount of time spent in Canada significantly influence dietary acculturation. 40 Likewise, dietary patterns -which include the quantity, variety, or combination of different foods and beverages in a diet, and the frequency with which they are consumed -have direct connections to food security, especially in relation to the consumption of meat, fruit, and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38] All studies involved participants who identified as immigrant, refugee, or migrant. [34][35][36][37][38] Specifically, two of the five studies included Somali immigrants and migrants, 36,37 two studies included African and Caribbean immigrant women, 34,38 and one of the five studies included participants described as African, Caribbean, or Black. 35 All studies focused on adults, who are classified as participants aged 16 years and older.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation